Perforated Neonatal Appendicitis with Massive Pneumoperitoneum: A Case Report - Jashari, Hysni J.; Hyseni, Nexhmi; Kelmendi, Baton; Hyseni, Fjolla; Kola, Ina; Vokshi, Valon; Martinez, Barbara; Rakovica, Loran; Guy, Ali; Musa, Juna (Archives of Clinical and Medical Case Reports, 2020)
Neonatal appendicitis (NA) is a rare condition. It has a low incidence of 0.04-0.2% and is more common in premature male babies. NA should be considered in the differential diagnosis in cases when a newborn does not present with clinical signs of Hirschsprung's disease, Cystic Fibrosis and passes meconium normally. The causative etiology of neonatal perforated appendicitis (NPA) is a subject of debate and has not been elucidated. Although many etiologic theories exist, increasing evidence suggests a subset of NPA cases may represent a form of necrotizing enterocolitis (NEC) localized to the appendix. A 6 days old male-baby presented at the NICU with generalized abdominal tenderness, the patient was febrile, with tachycardia and mild respiratory distress. The X-ray showed massive pneumoperitoneum. Intraoperatively, perforated appendix was found and appendectomy was performed. The abdomen was washed with ample saline and closed in layers. Neonatal appendicitis usually presents with non-specific symptoms and signs. Because of its rarity and low index of suspicion, it poses a great diagnostic challenge pre-operatively.